Avaliação da potencialidade dos resíduos de gesso de revestimento incorporados em formulações de massas cerâmicas - Silva, Jaquelígia Brito da (2008)
In building, during the implementation process of major or even minor works, there is a considerable waste of plaster in the steps of coating, making it is a negative factor because of the loss of these processes constructive remains incorporated into buildings, as component, whose final dimensions are higher than those projected. Another negative factor is the disposal of waste gypsum in inappropriate places, thus contributing to the degradation of environmental quality, due to the leaching of this waste and may trigger the formation of sulfuric acid. Therefore, based on this picture, processing and reuse of waste coating, combined with the ceramics industry, which is a strong potential in the reuse of certain types of waste, promote mutual benefits. Thus the overall objective of this work is to conduct a search with scientific and technological aspects, to determine the effect of the incorporation of the residue of plaster for coating, from the building, the formulation of bodies for red ceramic. The residue of plaster coating was collected and characterized. They were also selected raw materials of two ceramic poles of the state of Rio Grande do Norte and formulations have been made with the intention of obtaining those with the best physical and mechanical properties, the residue was added the percentage of 5%, 10%, 15%, 20%, 25% and 30%, in the best formulation of ceramic industry 1 and, according the properties analyses, 5%, 10% and 15% as the best results of ceramic industry 2. The samples were sintered at temperatures of 850 ºC, 950 °C and 1050 °C, the heating rate of 5 ºC / min with isotherm of two hours. They were submitted to testing technology, such as lineal shrinkage, water absorption, apparent porosity, apparent density and bending resistence. The residue incorporation best results in the formulations of mass in red ceramic, were observed between the temperatures of 850 ºC and 950 ºC, in those formulations that have illite clays and medium plastic in their composition, in the range of 0% to 15% residue incorporated